A Rebuttal to Harvey, R. (2016). 'Risks and Fallacies Associated with Promoting a Legalized Trade in Ivory' in Politikon 43(2): 215–229. (1st September 2016) - 't Sas-Rolfes, Michael
ABSTRACT: By framing contemporary policy debates as a superficial choice between two polarised approaches to global ivory trade legality, Harvey [2016. "Risks and Fallacies Associated with Promoting a Legalized Trade in Ivory." Politikon 43 (2): 215–229] oversimplifies and mischaracterises the nature of the African elephant conservation and trade regulation problem. Consequently, there is a failure to engage appropriately with the analytical work undertaken by economists and other social scientists since the 1989 ivory ban. Much of this work elucidates deeper institutional complexities relating to elephant management across different scales and geographies and acknowledges it as an issue of political economy as much as one of conservation. Over-simplifying the trade legalisation debate provides a distraction from more fundamental challenges facing the survival of Africa's elephants. To understand and address these challenges more appropriately, analysts and decision-makers should carefully consider the implications of conflicting values, institutional interplay and economic limits. Most importantly, they should work closer together to identify and resolve outstanding questions of mutual interest.